Nominalist Realism*. (20th March 2017) - Jones, Nicholas K.
Abstract: This paper explores the impact of quantification into predicate position on the metaphysics of properties, arguing that two familiar debates about properties are fundamentally altered by recasting them in a second‐order setting. Two theories of properties are outlined, differing over whether the existence of properties is expressed using first‐order or second‐order quantifiers. It is argued that the second‐order theory: (a) provides good reason to regard debate about the locations of properties as contentless; (b) resolves debate about whether properties are particulars or universals in favour of universals.